The role of the nervous system in neuromuscular fatigue induced by ultra-endurance exercise - Millet, G. Y.; Martin, V.; Temesi, J. (Applied Physiology, Nutrition, and Metabolism, 2018)
Ultra-endurance events are not a recent development but they have only become very popular in the last 2 decades, particularly ultramarathons run on trails. The present paper reviews the role of the central nervous system in neuromuscular fatigue induced by ultra-endurance exercise. Large decreases in voluntary activation are systematically found in ultra-endurance running but are attenuated in ultra-endurance cycling for comparable intensity and duration. This indirectly suggests that afferent feedback, rather than neurobiological changes within the central nervous system, is determinant in the amount of central fatigue produced. Whether this is due to inhibition from type III and IV afferent fibres induced by inflammation, disfacilitation of Ia afferent fibers owing to repeated muscle stretching or other mechanisms still needs to be determined. Sleep deprivation per se does not seem to play a significant role in central fatigue although it still affects performance by elevating ratings of perceived exertion. The kinetics of central fatigue and recovery, the influence of muscle group (knee extensors vs plantar flexors) on central deficit as well as the limitations related to studies on central fatigue in ultra-endurance exercise are also discussed in the present article. To date, no study has quantified the contribution of spinal modulations to central fatigue in ultra-endurance events. Future investigations utilizing spinal stimulation (i.e., thoracic stimulation) must be conducted to assess the role of changes in motoneuronal excitability on the observed central fatigue. Recovery after ultra-endurance events and the effect of sex on neuromuscular fatigue must also be studied further.